High-resolution breakpoint junction mapping of proximally extended D4Z4 deletions in FSHD1 reveals evidence for a founder effect. Issue 5 (24th September 2021) - Lemmers, Richard J L F; van der Vliet, Patrick J; Granado, David San Leon; van der Stoep, Nienke; Buermans, Henk; van Schendel, Robin; Schimmel, Joost; de Visser, Marianne; van Coster, Rudy; Jeanpierre, Marc; Laforet, Pascal; Upadhyaya, Meena; et al.
Abstract: Facioscapulohumeral muscular dystrophy (FSHD) is an inherited myopathy clinically characterized by weakness in the facial, shoulder girdle and upper a muscles. FSHD is caused by chromatin relaxation of the D4Z4 macrosatellite repeat, mostly by a repeat contraction, facilitating ectopic expression of DUX4 in skeletal muscle. Genetic diagnosis for FSHD is generally based on the sizing and haplotyping of the D4Z4 repeat on chromosome 4 by Southern blotting (SB), molecular combing or single-molecule optical mapping, which is usually straight forward but can be complicated by atypical rearrangements of the D4Z4 repeat. One of these rearrangements is a D4Z4 proximally extended deletion (DPED) allele, where not only the D4Z4 repeat is partially deleted, but also sequences immediately proximal to the repeat are lost, which can impede accurate diagnosis in all genetic methods. Previously, we identified several DPED alleles in FSHD and estimated the size of the proximal deletions by a complex pulsed-field gel electrophoresis and SB strategy. Here, using the next-generation sequencing, we have defined the breakpoint junctions of these DPED alleles at the base pair resolution in 12 FSHD families and 4 control individuals facilitating a PCR-based diagnosis of these DPED alleles. Our resultsshow that half of the DPED alleles are derivates of an ancient founder allele. For some DPED alleles, we found that genetic elements are deleted such as DUX4c, FRG2, DBE-T and myogenic enhancers necessitating re-evaluation of their role in FSHD pathogenesis.